Preserved thenar muscles in non‐ambulant Duchenne muscular dystrophy patients. Issue 3 (8th May 2021) - Naarding, Karin J.; Keene, Kevin R.; Sardjoe Mishre, Aashley S.D.; Veeger, Thom T.J.; van de Velde, Nienke M.; Prins, Arina J.; Burakiewicz, Jedrzej; Verschuuren, Jan J.G.M.; van der Holst, Menno; Niks, Erik H.; Kan, Hermien E.
Abstract: Background: Clinical trials in Duchenne muscular dystrophy (DMD) focus primarily on ambulant patients. Results cannot be extrapolated to later disease stages due to a decline in targeted muscle tissue. In non‐ambulant DMD patients, hand function is relatively preserved and crucial for daily‐life activities. We used quantitative MRI (qMRI) to establish whether the thenar muscles could be valuable to monitor treatment effects in non‐ambulant DMD patients. Methods: Seventeen non‐ambulant DMD patients (range 10.2–24.1 years) and 13 healthy controls (range 9.5–25.4 years) underwent qMRI of the right hand at 3 T at baseline. Thenar fat fraction (FF), total volume (TV), and contractile volume (CV) were determined using 4‐point Dixon, and T2water was determined using multiecho spin‐echo. Clinical assessments at baseline ( n = 17) and 12 months ( n = 13) included pinch strength (kg), performance of the upper limb (PUL) 2.0, DMD upper limb patient reported outcome measure (PROM), and playing a video game for 10 min using a game controller. Group differences and correlations were assessed with non‐parametric tests. Results: Total volume was lower in patients compared with healthy controls (6.9 cm 3, 5.3–9.0 cm 3 vs. 13.0 cm 3, 7.6–15.8 cm 3, P = 0.010). CV was also lower in patients (6.3 cm 3, 4.6–8.3 cm 3 vs. 11.9 cm 3, 6.9–14.6 cm 3, P = 0.010). FF was slightly elevated (9.7%, 7.3–11.4% vs. 7.7%, 6.6–8.4%, P = 0.043), while T2water was higher (31.5 ms, 30.0–32.6 ms vs. 28.1 ms, 27.8–29.4 ms, P < 0.001). Pinch strength and PUL decreased over 12 months (2.857 kg, 2.137–4.010 to 2.243 kg, 1.930–3.339 kg, and 29 points, 20–36 to 23 points, 17–30, both P < 0.001), while PROM did not (49 points, 36–57 to 44 points, 30–54, P = 0.041). All patients were able to play for 10 min at baseline or follow‐up, but some did not comply with the study procedures regarding this endpoint. Pinch strength correlated with TV and CV in patients (rho = 0.72 and rho = 0.68) and controls (both rho = 0.89). PUL correlated with TV, CV, and T2water (rho = 0.57, rho = 0.51, and rho = −0.59). Conclusions: Low thenar FF, increased T2water, correlation of muscle size with strength and function, and the decrease in strength and function over 1 year indicate that the thenar muscles are a valuable and quantifiable target for therapy in later stages of DMD. Further studies are needed to relate these data to the loss of a clinically meaningful milestone.